Local climate change policy in the United Kingdom and Germany - Harriet Bulkeley; Kristine Kern (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
For over a decade climate change has been considered one of the most significant political issues facing the international community. In order to address this challenge, attention needs to be focused not only at the international level of treaties and conventions, but also on how climate protection policy is taking shape at the local level. Germany and the UK have been leading countries for international action on climate change. However, the reductions in domestic emissions of greenhouse gas emissions achieved benefited in both countries from specific circumstances. This report details the national climate change policy, the structure of local governments, their competencies and powers, the institutionalisation of local climate change policy, the most important spheres of action and the different roles played by municipalities in local climate protection policy in both countries. – – Seit mehr als zehn Jahren wird der Klimawandel als eine der wichtigsten politischen Herausforderungen betrachtet, mit denen sich die internationale Gemeinschaft konfrontiert sieht. Um diese meistern zu können, darf sich die Aufmerksamkeit nicht nur auf Verträge und Konventionen auf der internationalen Ebene beschränken, sondern muss sich auch auf die Umsetzung des Klimaschutzes auf der lokalen Ebene richten. Deutschland und Großbritannien sind im Bereich des Klimaschutzes international führende Nationen. Allerdings wurde die Reduktion der Treibhausgasemissionen in beiden Ländern durch die jeweiligen Rahmenbedingungen erheblich begünstigt. Der vorliegende Bericht beschäftigt sich mit der nationalen Klimaschutzpolitik, der Struktur der Kommunen, ihren Zuständigkeiten, der Institutionalisierung der lokalen Klimapolitik, den wichtigsten Handlungsbereichen sowie mit den unterschiedlichen Rollen der Kommunen im Bereich des Klimaschutzes in beiden Ländern.
Keywords: 300